Dynapenia, gait speed and daily physical activity measured using triaxial accelerometer in older Japanese men - Masahiro Ikenaga; Yosuke Yamada; Noriko Takeda; Misaka Kimura; Yasuki Higaki; Hiroaki Tanaka; Akira Kiyonaga; Nakagawa Study Group (Japanese Society of Physical Fitness and Sports Medicine, 2014)
This cross-sectional study was performed to determine the relationship between the intensity of daily physical activity (PA) assessed by triaxial accelerometer (ACCtri) and muscle strength or gait speed. We measured the hand grip strength (HGS) and knee extension strength (KES) as well as preferred gait speed (PGS) and maximal gait speed (MGS) of a total of 178 community-dwelling elderly men aged 70-79 years. The duration and intensity of PA were evaluated by ACCtri on eight consecutive days, and the total duration of each level of activity intensity (Inactivity, Light PA: LPA, Moderate PA: MPA, and Vigorous PA: VPA) and daily step count were also measured. After adjustment for age, body mass index (BMI) and body fat percentage, KES and MGS were significantly correlated with step count. The duration of MPA was correlated with KES (r = 0.208, P < 0.01) and MGS (r = 0.213, P < 0.05). PGS and HGS were not significantly correlated with any PA parameters. MPA and step counts were significantly, but weakly, related to KES and MGS. The results suggest that a longer time spent on either daily ambulatory activity or MPA may be associated with age-associated loss of muscle strength (dynapenia) and gait decline in older men.